Kriya Tekstil Rumahan: Strategi Bertahan di Masa Pandemi Covid-19 - Limono, Lusiana (Sekolah Pascasarjana Institut Kesenian Jakarta, 2023)
The pandemic has disrupted the rhythm of life, especially the rhythm of urban people's lives. Women, often experience a double burden. This is because the center of activity shifted to home. Working from home, school from home, making mothers busy, women at home become overwhelmed. Urban women need to maintain both physical and psychological health to manage their minds to stay positive. Positive thinking is needed to deal with pressure and uncertain conditions, and it is not yet known when it will end. One of the activities that dominates the most activities at home during the pandemic is activities characterized by crafts / hand skills, such as embroidery, knitting, patchwork. This paper traces women's activities during the pandemic which focused on home textile crafts. The aim is to find out what benefits are obtained from these activities and what values make them so attractive to urban women. The search uses practice-based research methods through literature, observations on social media, interviews, and practice in the studio. Improving the quality of life, releasing tension, maintaining 'sanity', pleasant time for yourself is some of the qualities gained from home textile craft activities.